Inverse Determination of Thermal Conductivity in Wood of Pinus Rathata - Vasco-Calle, D (UNIV BIO-BIO, 2018)
Laboratory scale experiments are performed in order to characterize the artificial wood drying of Pinus radiata at conventional temperatures and accelerated temperatures. The experimental data allow determining the wood thermal conductivity through inverse methodology. The comparative analysis shows that the implementation of the developed inverse methodology is consistent with information available in the specialized literature; which means increased thermal conductivities with increased humidity and temperature, whose values oscillate between 0,34 and 0,56 (W/m K) to moisture variations between 22% and 64%; and temperatures between 70 degrees C and 90 degrees C, respectively.